RESPUESTA AGRONÓMICA DEL CULTIVO DE PIMIENTO (Capsicum annuum L.) BAJO EL EFECTO DE LA APLICACIÓN DE COMPUESTOS BIOLÓGICOS - Zamora Soriano, Leidy Selena (2023)
Bell pepper production in Ecuador has generated an increase in the use of organic fertilizers to improve crop yields, which has generated certain levels of toxicity in the soil and plants. Over time, the use of organic alternatives has been sought to replace these products, such as the application of products based on microorganisms and marine algae, which contain phytohormones such as auxins, gibberellins and cytokinins, which promote plant growth and development.